Pengaruh Pengetahuan Parenting Terhadap Keterlibatan Orang Tua Di Lembaga PAUD - Wilda Azkiyah; Vina Farhatunnisa Haryono; Windy Nur Fitriyyah; Fidrayani Fidrayani (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
Parents who don't know about parenting can make communication between parents and teachers difficult. The parenting program is an effort to increase parents' knowledge in meeting the basic needs of early childhood. This research aims to compare several aspects of research results on the influence of parenting knowledge on parental involvement in PAUD institutions between 2019 and 2024. The method used is The type of research used in this research is descriptive quantitative and was designed using a regression approach with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) method and the results of the Effect Size calculation. This research shows that parents who understand parenting are very important. Parenting knowledge with parental involvement is very significant with an average of 1.17%